Features of microstructure of carbide blanks - O. Yu. Khodosovskaya; L. V. Ovsyanikova; T. V. Gapeenko (Литьë и металлургия)
The task of modern science and technology is to develop new and improve the characteristics of already used materials for the production of competitive products. Due to the reorientation of sales markets and the search for alternative suppliers of carbide tools, OJSC “BSW – Management Company of “BMK” Holding” began cooperation with Chinese firms‑manufacturers/ suppliers of carbide blanks. The article examines the features of the microstructure of carbide blanks. The blanks differ from the serially used blanks in microstructure, in particular, in the class of tungsten carbide grain. This is explained by the fact that grades of alloy with nanoscale tungsten carbide grain are used for the production of blanks to achieve the necessary durability during operation. The features in the microstructure of the hard alloy also led to changes in the “density” parameter towards reduction, which is also inherent in all Chinese blanks and does not affect their operational properties. Inhibitors of grain growth – transition metal carbides, for example, VC, Cr2C3, NbC, TaC are added to hard alloy mixtures to prevent grain growth during sintering. Recently, there has been a trend towards introducing TaC + TiC additives into WC–Co alloys, which prevent grain growth and have a negligible effect on all other properties of hard alloys.